Design, Simulation and Comparison of Controllers That Estimate an Hydric Balance in Strawberry Plantations in San Pedro - Viera-Riquelme, E; Gonzalez-Ortega, A (Springer Science and Business Media Deutschland GmbH, 2020)
This work has a great relevance in modern agriculture, because of the nowadays problematic of the hydric resources at national and world level. Which evaluates different control technics able to estimate an hydric balance in strawberry plantations. Through the PID controllers with neural networks and diffuse logic. Getting better results with neural networks in Adequation Index, Settling Time, Overshoot and Stability, with which the obtained results were validated. © 2020, Springer Nature Switzerland AG.